2020
DOI: 10.1136/bmjoq-2019-000803
|View full text |Cite
|
Sign up to set email alerts
|

Quality improvement in forensic mental health: the East London forensic violence reduction collaborative

Abstract: Ward-based violence is the most significant cause of reported safety incidents at East London NHS Foundation Trust (ELFT). It impacts on patient and staff safety, well-being, clinical care and the broader hospital community in various direct and indirect ways. The contributing factors are varied and complex. Several factors differentiate the forensic setting, which has been identified as a particularly stressful work environment. Staff must constantly balance addressing therapeutic needs with robust risk manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Using QI to empower staff and service users to work together to address this issue has been a source of inspiration for other wards within our service. This violence reduction collaborative has since been scaled-up considerably across the Trust and, indeed, into other psychiatric sub-specialities such as forensic mental healthcare (O'Sullivan et al, 2020).…”
Section: Collaboration and Communicationmentioning
confidence: 99%
“…Using QI to empower staff and service users to work together to address this issue has been a source of inspiration for other wards within our service. This violence reduction collaborative has since been scaled-up considerably across the Trust and, indeed, into other psychiatric sub-specialities such as forensic mental healthcare (O'Sullivan et al, 2020).…”
Section: Collaboration and Communicationmentioning
confidence: 99%
“…Particularly noteworthy is the analysis of the phenomenon of domestic violence in six European countries, in which Costa et al (2015) proved that both men and women are equally likely to become victims and perpetrators of domestic violence [ 27 , 28 ]. However, it is worth noting that men are increasingly admitting to being victims of domestic violence, which is probably related to cultural changes and breaking taboos [ 29 , 30 , 31 ]. A similar analysis by Lindert et al (2011) of seven European cities found that women are more likely to be victims of violence in the older population (60–84 years) but significantly more likely to be psychological and economic rather than physical [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 The ability to use a safe, supportive place to articulate concerns is essential to build high expectations and standards within a culture of transparent error disclosure so that safe health care can be provided. 9,15 For example, Sullivan et al 4 found an 8% to 16.6% reduction in physical and nonphysical violent incidents in psychiatric wards over 2 years after implementing collaborative learning and huddles.…”
Section: T Has Been 20 Years Since the Publication Ofmentioning
confidence: 99%
“…2 Other patient populations, including those with psy-chiatric conditions, have unique patient safety issues, such as risks of self-harm, restraint injuries, or violence that may be preventable if organizational safety strategies are employed. [3][4][5] In the United States, 115 out of every 1000 hospitalizations result in a preventable safety event, with a cost to payers averaging $8000 per admission. 6 A systematic review and metaanalysis across a range of health care settings globally estimated that about one in 20 patients experience preventable harm related to health care.…”
Section: T Has Been 20 Years Since the Publication Ofmentioning
confidence: 99%
See 1 more Smart Citation